PENGARUH FREE CASH FLOW DAN DEBT TO EQUITY RATIO TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN SUB SEKTOR FARMASI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Marismiati, Marismiati; Hamidah, Nayla (Universitas Logistik dan Bisnis Internasional, 2025)
The rapid economic and business developments currently occurring have caused intense competition for every company. With competition, companies are required to be more progressive and improve their performance to achieve company goals. Company value is often linked to share prices, the higher the share price, the higher the company value, and vice versa. Pharmaceutical companies experienced a decline in share prices after the Covid-19 pandemic ended. This can affect company value. The aim of this research is to determine the influence of Free Cash Flow and Debt Policy on Company Value in pharmaceutical Sub-Sector Companies Listed on the Indonesian Stock Exchange. This research sample used a purposive sampling technique with 40 samples of financial reports from pharmaceutical sub-sector companies listed on the Indonesian Stock Exchange, which were obtained from the financial reports of pharmaceutical sub-sector companies listed on the Indonesian Stock Exchange and processed using SPSS with, Product Moment test Correlation, Multiple Correlation, Multiple Regression Analysis, Coefficient of Determination, t Test (partial), and Uj F (simultaneous) using IBM SPSS Statistics Version 27. The results of this study explain that there is no partial influence between Free Cash Flow on Company Value, whereas Debt policy partially has an influence on company value, and simultaneously Free Cash Flow and Debt to Equity Ratio have an influence on company value in pharmaceutical sub-sector companies listed on the Indonesia Stock Exchange.